2015
DOI: 10.1007/s11845-015-1348-8
|View full text |Cite
|
Sign up to set email alerts
|

Propofol-ketamine combination: a choice with less complications and better hemodynamic stability compared to propofol? On a prospective study in a group of colonoscopy patients

Abstract: Propofol-ketamine combination is an advantageous choice in means of achieving sedation in a shorter period of time, a better hemodynamic stability, less nausea and vomiting and respiratory complication rates. Yet it seems that this choice might be related with longer recovery duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“… 19 It has been suggested that when propofol is added to ketamine, it reduces these effects by sympathetic neutralization and hemodynamic stabilization. 19 - 22 In this study, we observed similar hemodynamic stabilization. Owing to the cardio-depressive effects of both propofol and alfentanil, the combination of these drugs results in hemodynamic instability.…”
Section: Discussionsupporting
confidence: 81%
“… 19 It has been suggested that when propofol is added to ketamine, it reduces these effects by sympathetic neutralization and hemodynamic stabilization. 19 - 22 In this study, we observed similar hemodynamic stabilization. Owing to the cardio-depressive effects of both propofol and alfentanil, the combination of these drugs results in hemodynamic instability.…”
Section: Discussionsupporting
confidence: 81%
“…[25] The use 0.5 mg/kg of ketamine with or without propofol may eliminate emergence reactions. [28][29] We did not observe emergence reactions in any patient after the procedure because of low-dose ketamine combined with propofol.…”
Section: Discussionmentioning
confidence: 69%
“…[32] Previous studies have revealed that the use of larger initial bolus doses of propofol was associated with higher incidence of hypotension. [22][23][24][25][26][27][28][29][30] Hsieh et al [21] reported hypotension incidence as 23% for an initial bolus of 1 mg/kg propofol, which was then titrated in 10-20 mg increments plus 25 mg of meperidine (dose of propofol, 129.80±37.93 mg). In contrast, Sáenz-López et al [30] reported no hypotension for an initial bolus of 20 mg of propofol, followed by boluses of 10 mg every 30 s plus 25-50 mg of meperidine (dose of propofol, 66.93 mg).…”
Section: Discussionmentioning
confidence: 99%
“…The sedative patients were discharged from the RR when they met discharge criteria (23). The probability of early discharge from PACU is an essential feature in the care of outpatients and produces better service and lower costs (24).…”
Section: Discussionmentioning
confidence: 99%